The creative tension between statistics and economics - Cheng, Hsiao. (2013)
This paper warns the risks of uncritically adopting the mind set of statisticians in empirical analysis. The examples of vector autoregressions, forecast combinations and measurement of treatment effects are used to illustrate the fragility of statistical inference when sample observations are limited.